2004
DOI: 10.2149/tmh.32.245
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility and Its Genetic Analysis of Vibrio Cholerae Non-O1, Non-O139 From Environmental Sources in Lao People's Democratic Republic

Abstract: In order to determine the epidemiological features of cholera in Lao PDR, the presence of mobile genetic elements such as plasmid, class I integron and SXT element in V. cholerae isolated from surface water were examined. Among the 22 strains isolated from 13 distantly separated sampling sites, no mobile genetic elements associated with drug resistance were found reflecting the antibiogram of the strains. Nevertheless, cholera epidemics due to multiple drug resistant V. cholerae occurred repeatedly in those ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…The changing landscape of antibiotic resistance in pathogenic bacteria associated with diarrhoeal patients in Indonesia was documented by Tjaniadi et al (2003). The presence of ampicillin-resistant V. cholerae isolates in this study appeared to be similar to that found in Laos, where both non-O1 and non-O139 isolates were found to be resistant to ampicillin (Miyazato et al, 2004).…”
Section: Prevalence Of V Cholerae Non-o1 Serogroups In Edible Icesupporting
confidence: 75%
See 1 more Smart Citation
“…The changing landscape of antibiotic resistance in pathogenic bacteria associated with diarrhoeal patients in Indonesia was documented by Tjaniadi et al (2003). The presence of ampicillin-resistant V. cholerae isolates in this study appeared to be similar to that found in Laos, where both non-O1 and non-O139 isolates were found to be resistant to ampicillin (Miyazato et al, 2004).…”
Section: Prevalence Of V Cholerae Non-o1 Serogroups In Edible Icesupporting
confidence: 75%
“…There has been an increase in the incidence of antibiotic resistance in O1, O139 and non-O1 V. cholerae serogroups in both clinical and environmental isolates (Deashinta et al, 2007;Mandal et al, 2012;Rahmani et al, 2012;Panda et al, 2012). V. cholerae O1 strains that are resistant to cefotaxime, nalidixic acid, streptomycin, tetracycline and trimethoprim have been isolated from south India (Jagadeeshan et al 2009), andIwanaga et al (2004) reported V. cholerae O1 strains from a patient in Laos resistant to chloramphenicol, tetracycline, streptomycin and trimethoprim.…”
Section: Introductionmentioning
confidence: 99%
“…Waldor et al [1996] identified in V. cholerae O1 and O139 an approximately 62 kb self-transmissible, chromosomally integrating genetic element, which was found to contain genes encoding resistance to sulphonamides, trimethoprim and streptomycin [ 11 ]. However, the antibiotic susceptibilities of organisms fluctuate spatially and temporally [ 19 ]. These susceptibilities have to be examined in order to better understand the organisms' epidemiological features [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resistant genes for these two antibiotics are known to be encoded by SXT element. The reason that not all SXTint isolates were resistant to SXT and streptomycin could be the finding that the SXT element may acquire the resistance genes through horizontal transfer (Miyazato et al, 2004). Therefore, the presence of SXT element should be monitored even in drug susceptible V. cholerae isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the presence of SXT element should be monitored even in drug susceptible V. cholerae isolates. Miyazato et al (2004) have indicated that no mobile genetic elements such as plasmid, class I integron or SXT element was detected in 22 environmental non-O1, non-O139 strains which were isolated from 13 distant sampling sites in Vietnam. In conclusion, the data presented in this study showed that the SXT-C element intrinsically harboring several different antibiotic resistance gene cassettes is widely distributed among different clinical and in acceptable number, in environmental V. cholerae in Iran.…”
Section: Discussionmentioning
confidence: 99%